Edible Coatings Formulated with Antifungal GRAS Salts to Control Citrus Anthracnose Caused by Colletotrichum gloeosporioides and Preserve Postharvest Fruit Quality - Martínez-Blay, Victoria; Pérez-Gago, María B.; De-La-Fuente, Beatriz; Carbó, Rosario; Palou, Lluís (MDPI, 2020)
The in vitro antifungal activity of various generally recognized as safe (GRAS) salts against Colletotrichum gloeosporioides, the causal agent of citrus postharvest anthracnose, was evaluated as mycelial growth reduction on potato dextrose agar (PDA) dishes amended with salt aqueous solutions at different concentrations. The most effective treatments [0.2% ammonium carbonate (AC), 2% potassium sorbate (PS), 0.2% potassium carbonate (PC), 0.1% sodium methylparaben (SMP), 0.1% sodium ethylparaben (SEP), 2% sodium benzoate (SB) and 2% potassium silicate (PSi)] were selected as antifungal ingredients of composite edible coatings formulated with hydroxypropyl methylcellulose (HPMC)-beeswax (BW) matrixes. Stable coatings containing these salts were applied in in vivo curative experiments to “Nadorcott” mandarins and “Valencia” oranges artificially inoculated with C. gloeosporioides and those containing 2% PS, 2% SB and 2% PSi were the most effective to reduce anthracnose severity with respect to control fruit (up to 70% on mandarins). The effect of these selected coatings on the quality of non-inoculated and cold-stored “Valencia” oranges was determined after 28 and 56 days at 5 ºC and 90% RH, followed by 7 days of shelf life at 20 ºC. None of the coatings significantly reduced weight loss of coated oranges, but they modified their internal atmosphere, increasing the CO2 content. Overall, the coatings did not adversely affect the physicochemical and sensory attributes of the fruit.